Comparances in Quality of Chocolate Mousse Using Chocolate Compound with Chocolate Couverture - Fika Yulianti Fasha; Rusilanti; Guspri Devi Artanti (Jurnal Sains Boga, 2023)
The purpose of this study is to analyze and compare the sensory quality of chocolate mousses made from two kinds of chocolate, namely compound and couverture. This study was conducted in the Pastry Laboratory, Culinary Arts Study Program, Faculty of Engineering, Universitas Negeri Jakarta from December 2019 to January 2022. This study used the experimental research method. U Mann Whitney test results show that there are significant differences in the sensory quality aspects with a significance level of α = 0.05.The analysis results show that the higher average scores between the two kinds of chocolate are as follows: in the color aspect was 3.4 for couverture chocolate (dark brown category), in the aroma aspect was 4.2 for couverture chocolate (somewhat strong chocolate aroma category), in the taste (sweetness) aspect was 4.5 for compound (sweet category), in the taste (chocolate flavor) aspect was 4.76 for couverture chocolate (rich chocolate flavor category), and in the texture aspect was 4.5 for compound chocolate (soft texture category). It is concluded that there are significant differences in color, aroma, taste (sweetness), and taste (chocolate flavor) aspects of sensory quality and no significant difference in the texture aspect.